The Effect of Shuttle Run Training on Agility Students' Gobak Sodor Game - Ayi Rahmat; Andrian Rahman Ayudi; Taufik Hidayat Suharto, (Cirebon Annual Multidiciplinary International Conference (CAMIC), 2025)
The research was conducted to determine the effect of Sutle Run training on agility in gobak sodor sports players at Setia Budhi University Rangkasbitung. So a research was conducted, as an effort to find out the effect of Sutle Run training methods carried out on these students through Agility tests on gobak sodor Sports Players. The effect of Sutle Run Training on Agility in Gobak sodor Sports Players at Setia Budhi University Rangkasbitung was conducted. The research uses quantitative research. The method used is an experimental method. The variable of this research is the effect of Sutle Run training on agility in the gobak sodor sports players at Setia Budhi University Rangkasbitung, totaling 20 students. The results of the research show that the t value is 3,933 with df 19. Then the t score is consulted with the t table at a significance level of 5% and df 19 is 2,093. This shows that the calculated t is greater than the t table (3,393> 2.093). From the table it is known that the p value = 0.000, this shows sig. (2-talled) < 0.05. It can be seen from the difference in the average value of the pretest and posttest which is 10.85 and 10.24 which is smaller after being given Shuttle Run Training on Agility in Gobak sodor Sports Players at Setia Budhi University Rangkasbitung by 5.62%. It can be concluded that there is an influence.